2017
DOI: 10.1111/sum.12333
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil phosphorus pools of grasslands following 17 yrs of balanced application of manure and fertilizer

Abstract: Limiting the use of phosphorous (P) in intensive agriculture is necessary to decrease losses to surface waters. Balanced fertilizer application (P supply equals P offtake by the crop) is a first step to limit the use of P. However, it is questioned whether this balance approach is sufficient to maintain soil fertility. A long-term field experiment (17 yr), on grazed grassland, has been conducted on sandy soil, marine clay soil and peat soil to obtain insight into the effects of balanced P fertilizer applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…P supply will limit increases in agricultural production worldwide in the coming decades. Excessive usage of fertilizers to overcome P deficiency has led to many problems, such as P accumulation in the soil system and surface water runoff [ 3 , 4 ]. Red soils, having a low or acidic soil pH, are widely distributed in the southern part of China.…”
Section: Introductionmentioning
confidence: 99%
“…P supply will limit increases in agricultural production worldwide in the coming decades. Excessive usage of fertilizers to overcome P deficiency has led to many problems, such as P accumulation in the soil system and surface water runoff [ 3 , 4 ]. Red soils, having a low or acidic soil pH, are widely distributed in the southern part of China.…”
Section: Introductionmentioning
confidence: 99%
“…P is one of the most important elements in the biosphere and agriculture, especially for promoting plant growth (Quanxian et al, 2008). However, excessive use of phosphate fertilizers induces remineralization iScience Article and P accumulation in soils; only a small and variable fraction of the added P is directly available to the plants ( Van der Salm et al, 2017). It is because soil contains a large amount of iron and aluminum oxides, and once applied phosphate fertilizer enters the soil, it will be fixed to form insoluble P (Yang et al, 2021a).…”
Section: Enhancement Of Nutrient Availabilitymentioning
confidence: 99%
“…This reflects the differences in P pools measured by these tests: P‐AL is a more buffered method, whereas the aggressive ammonium oxalate extraction is a measure for total soil P. That ΔP‐Ox exceeds the cumulative shoot P uptake (+N treatment) can be partly explained by underestimation of the total cumulative P uptake because the P uptake by roots was not included. Alternatively, part of the extractable P at the start of the pot trial can become unavailable for the acid ammonium oxalate extraction because of a transformation to non‐extractable P forms, for example because of the stronger binding and accumulation of P in inorganic forms or in organic material (Van der Salm et al ., ). For the +P treatment, the mass balance (calculated as P fertilizer application minus cumulative P uptake) was positive (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…A similar gap between the mass balance and Δ P values has been observed in other pot trials for the oxalate (Koopmans et al ., ) and Olsen extractions (Schelfhout et al ., ). In field studies, a decrease in soil P availability larger than the mass balance has also been observed (Gallet et al ., ; Van der Salm et al ., ). In the present study, the mass balance of the Olsen extraction was smaller than the cumulative P uptake.…”
Section: Discussionmentioning
confidence: 97%